Dalil Jujur Dalam Perkataan Dan Perbuatan - Damanik, Muhammad Zein; Putri, Dhea Melati; Warda, Mutia Alamiah (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
Honesty is a fundamental moral value in the lives of individuals and society. In the context of Islamic education, particularly in the study of the Qur'an and Hadith, reinforcing the value of honesty becomes one of the main objectives for shaping noble character in students. This article discusses the concept of honesty in Islam based on verses from the Qur'an and the Hadith of the Prophet Muhammad (peace be upon him), as well as its implementation in the learning process. This research employs a qualitative approach using literature review methods to examine verses and hadiths that emphasize the importance of honesty in words and actions. The findings indicate that honesty is one of the essential qualities required of every Muslim, as stated in various verses of the Qur'an such as Surah An-Nahl: 91-92, along with hadiths that link honesty to closeness to Allah (SWT). In the study of the Qur'an and Hadith, integrating values of honesty can be achieved through teaching strategies that focus on understanding meanings, applying them in daily life, and providing role models from educators. Thus, education on honesty within the study of the Qur'an and Hadith is expected to cultivate students who are honest in their words and actions, contributing to the creation of an integrity-driven society.